The structural planning of the girder pci girder spanning 25.90 m Pier 20-21 on the Cimanggis - Cibitung Cctw 2 Toll Road Project - Syella Surviyanda Islami (Jakarta Global University, 2022)
This Bridge Structure Planning is a development which is located on the main road in the MM2100 area. With this planning aims to overcome the problem of congestion in this location. The girder planning with a span length of 25.90 meters was built using Precast Concrete I Girder. The required technical data is the span’s length, the road’s width, and the road’s class. The basis for planning this bridge refers to the regulations of SNI 1725: 2016, SNI 2833: 2016, and SNI 2847: 2019. The calculated loads are dead, live, traffic, and environmental. In this plan, the Microsoft Excel program is used to facilitate the analysis of the PCI-Girder structure. The result of this plan is to get the shape and dimensions of the long-span PCI Girder that supports the load acting on the bridge structure to obtain a safe bridge structure.